Popularity Ranking of Undergraduate Thesis Manuscripts in the E-Read System Based on Number of User Accesses (Nusantara Science and Technology Proceedings, 2021)
The undergraduate thesis is a scientific work produced by a final year student who collaborates with his supervisor as a condition to be able to complete his studies at a university. The increase in the number of thesis works has caused the library at the Faculty of Computer Science, UPN "Veteran" Jawa Timur to start overcapacity in accommodating the physical thesis books from each student, therefore in another part of the research conducted by the author, an undergraduate thesis book management system has been created in the library of the Faculty of Computer Science UPN "Veteran" Jawa Timur, which is named E-Read. Through the system built, all student undergraduate thesis works can be stored in digital form so that the problem of overcapacity of student physical books can be handled and provides convenience in managing and accessing the thesis data. This study aims to add a ranking feature for thesis manuscripts stored in the E-Read system database based on the popularity of the number of undergraduate theses works accessed by system users. Through this ranking feature, the users of the E-Read system, especially students, can find out the works that are most frequently accessed by other users so that they can provide more references to give ideas in finding the research topic that they will be working on. Based on the tests carried out, it can be stated that the system has fulfilled all functional requirements and has a very satisfactory usability value by producing a value above 3 for 12 attributes, and a value of 2.8 for 1 attribute.